Vesicoscopic Cross-Trigonal Ureteral Reimplantation for Vesicoureteral Reflux: Intermediate Results - Christian Kruppa; Guido Fitze; Katrin Schuchardt (Children, 2022)
For the treatment of vesicoureteral reflux, the introduction of vesicoscopic procedures offers new perspectives for improving patient comfort and quality. Our aim was to examine whether minimally invasive vesicoscopic cross-trigonal ureteral reimplantation (VCUR) would meet expectations. Between 2012 and 2021, 99 girls and 35 boys with high-grade vesicoureteral reflux (VUR) underwent VCUR. For two boys, we failed to establish the pneumovesicum, leading to conversion to open surgery. The mean age was 4.5 years, ranging from 10 months to 18 years. VCUR was successfully performed in 132 patients, including 75 patients with bilateral VUR and 12 children with double ureters with unilateral or bilateral VUR, corresponding to a total of 229 operated ureters. The mean time of operation was 151 min for all patients. There were no perioperative complications, with the exception of three cases of pneumoperitoneum without consequences. Postoperatively, we recognized three cases of acute hydronephrosis, two of them required transient drainage. Three patients developed extravasation of urine after the postoperative removal of the transurethral catheter, rapidly resolved by new drainage. In two patients, we combined VCUR with laparoscopic heminephrectomy and opposite laparoscopic nephrectomy, respectively. Overall, mean postoperative hospital stay was 4.2 days. We observed recurrent VUR in seven ureters, resulting in a success rate for VCUR of 96.9%. These results demonstrate the feasibility of VCUR and its potential to displace open surgery with high safety and wide applicability.